Analysis of the Jarimatika Method on the Ability to Count on Multiplication Material at the Intan Baiduri Tutoring Studio, Selayang, Kuala Lumpur - Ananda, Vina Rizky; Mestika Dewi, Ike Yuli; Kuswandi, Iwan (JUPE : Jurnal Pendidikan Mandala, 2025)
During the learning process, obstacles often arise or appear to monitor students' self-developing numeracy skills, especially at the elementary school level. Researchers found that the level of numeracy knowledge of students at the Intan Baiduri Selayang tutoring studio, Kuala Lumpur in multiplication material was relatively low. This research aims to analyze the use of the Jarimatics method in the ability to calculate multiplication material at the Intan Baiduri Selayang tutoring studio, Kuala Lumpur. This research applies a qualitative approach. The data collection methods applied include interviews, observation and documentation. The results of the research indicate that the learning process that utilizes this is proven by the low numeracy skills, the Jarimatics method is effective so that students have a significant understanding of the multiplication material. This can be seen from the attitude of students who are more active, enthusiastic and enthusiastic when participating in learning using the Jarimatika method, rather than the usual lecture or textbook method.